Model Profesionalisme Guru Berbasis Nilai Qur’ani: Studi Fenomenologi di Sekolah Dasar Islam Terpadu - Mana Sikana, Arina; Paryanti, Paryanti; Shaimah, Atik; Suryono, Suryono; Sabirin, Ego; Supandi, Supandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Teachers play a strategic role in the educational process as they are responsible for shaping students’ character and abilities; therefore, teacher professionalism is a key indicator of educational success. However, existing studies on teacher professionalism have predominantly focused on normative competencies and educational policies, while investigations that examine teacher professionalism based on Qur’anic values, particularly through a phenomenological approach, remain limited. This study aims to explore and understand teacher professionalism from the perspective of the Qur’an through a phenomenological study conducted at SDIT Al Hikam Banyudono. This research employed a qualitative descriptive method with a phenomenological approach. Data were collected through observation, interviews, and documentation, drawing on the Qur’an, textbooks, scientific journals, and other relevant documents. The findings indicate that teacher professionalism from the Qur’anic perspective is reflected in mastery of instructional content, compassionate attitudes toward students, gentleness in understanding students’ psychological conditions, physical well-being, and firmness in enforcing discipline. These findings contribute conceptually to the development of Islamic teacher professionalism studies by emphasizing that professionalism is not merely oriented toward technical competence, but also toward the internalization of Qur’anic values in educational practice.